THE DETERMINANT ACCOUNTABILITY OF VILLAGE FUNDS MANAGEMENT (Study in the Villages in Wonogiri District) - Triyono, Triyono; Achyani, Fatchan; Arfiansyah, Mufti Arief (Universitas Muhammadiyah Surakarta, 2019)
This study aims to determine the effect of financial statement presentation, accessibility of financial statements, quality of supervision of BPD, capacity of village apparatus, village financial system (Siskeudes), Government Intern Control System (SPIP) on accountability of village fund management. This study uses a quantitative approach. The population in the study were villages in Wonogiri Regency. Sampling using saturation sampling technique. Respondents in this study were the village head and village secretary. For the process of collecting data used the questionnaire method. Whereas to analyze data used multiple regression analysis.The results of the study show that 1) The presentation of financial statements has no effect on the accountability of village fund management. 2) Accessibility of financial statements does not affect the accountability of village fund management. 3) Quality of BPD Supervision does not affects the accountability of village fund management. 4) The capacity of the village apparatus does not influences the accountability of village fund management. 5) Village Financial System (Siskeudes) influences the accountability of village fund management. 6) The Government's Intern Control System (SPIP) has an effect on the accountability of village fund management.Keywords: Presentation of Financial Statements, Accessibility of Financial Reports, Quality of BPD Supervision, Capacity of Village Apparatus, Village Financial System, Government Internal Control System, Accountability of Village Fund Management.